Assessing Human and Organizational Risk in Upstream Oil and Gas Supply Chains: an ISO 31000 Perspective - Warashinta Nur Wulan Muthmainah; Popong Nurhayati; Sendy Watazawwadu'Ilmi (School of Business, IPB University (SB-IPB), 2026)
Background: Operational risk management in the upstream oil and gas sector demands a rigorous, integrated approach, particularly within supply chain administration where both technical and non-technical risk factors converge. PT Pertamina Hulu Energi (PHE) Jambi Merang, an upstream natural gas producer in South Sumatra, existing practices still tend to prioritize technical hazards while paying less attention to human and organizational factors.Purpose: This study aims to identify and evaluate operational risks within the supply chain administration of PHE Jambi Merang, and to formulate risk treatment strategies based on the ISO 31000:2018 framework.Design/Methodology/Approach: A qualitative descriptive approach was employed, utilizing in-depth interviews, field observation, and questionnaire distribution with five key respondents selected through purposive sampling using a RACI matrix. Risk assessment employed Godfrey (1996) probability and impact scales, with geometric mean aggregation and a 5x5 risk mapping matrix. Risk treatment strategies were formulated based on Flanagan and Norman (1993) typology.Findings/Result: Twenty-five operational risks were identified across four categories: internal, human resources, technical or system, and external risks. Three risks were classified as extreme, nine as high, eleven as medium, and two as low. The most critical risks include insufficient workforce competency, non-compliance with Corporate Life Saving Rules, and illegal oil and gas activities.Conclusion: The findings indicate that human and organizational factors represent the most critical operational risk exposures in upstream gas supply chain administration.Originality/Value: This study applies ISO 31000:2018 with explicit attention to human and organizational factors in upstream oil and gas supply chain administration in Indonesia. Keywords:human and organizational factors, ISO 31000:2018, operational risk management, supply chain, upstream oil and gas